Empowerment strategy analysis deep sharia cooperative liberate public from trap loan shark - Harahap, Siti Khodijah; Siagian, Salsabilla; Batubara, Maryam (STIE AMKOP, 2023)
Sharia cooperative play role important in clean public from practice dangerous Sharia. Moneylender often utilise public with ethnic group flower height and condition no credit profitable. The purpose of this paper is analize empowerment strategies sharia cooperative for liberate public from slavery to moneylender. Is known that calculated F value of 166.698 with level significance of 0.00 < 0.05. Then the regression model can used for predict variable impact and perception (X) of empowerment (Y). In other word variable impact and perception (X) of influential in a manner together to variable empowerment (Y) or H1 is accepted. mark significant is 0.00 < 0.05 means impact and perception influential in a manner positive and significant to empowerment. Means reject Ho and accept Hi. Equality the regression is Y= 4.693 + 0.287 X, that is If improved impact and perception as big One unit will increase of 0.287. Keywords: sharia cooperatives; loan sharks; empowerment